Evaluation of mother and daughter root traits in sweet potato germplasm cultivated by direct planting. (3rd July 2022) - Sakaigaichi, Takeo; Suematsu, Keisuke; Terajima, Yoshifumi; Kobayashi, Akira; Kawata, Yukari; Kai, Yumi
ABSTRACT: Direct planting (i.e. the planting of seed roots) in sweet potato results in the formation of two root types – 'mother' and 'daughter' roots. High and stable daughter root yields are necessary to improve the acceptance of direct planting cultivation because mother roots have no commercial value. To establish a basis for the effective breeding, the root traits of 28 sweet potato genotypes cultivated by direct planting were evaluated for mother root weight, daughter root weight (DRW), total root weight (TRW), ratio of DRW to TRW (RDRW), and ratio of mother root enlargement. Significant differences between the genotypes were observed for all five traits (p < 0.01). However, we concluded that RDRW is a reliable indicator for performance under direct planting cultivation because it showed the highest estimated heritability (0.57), and genotypes with high RDRW also indicated notably low values for coefficient of variation. Graphical abstract: uf0001